Pengembangan LKPD Berbasis Engineering Design Process untuk Meningkatkan Keterampilan Kolaborasi pada Siswa SMP - Dyah Astiari Rizky; Nur Ahmad; Rusdianto Rusdianto (Universitas Muhammadiyah Mataram, 2025)
Abstract: This study aims to determine the validity, practicality, and effectiveness of LKPD based on Engineering Design Process (EDP) to improve students' collaboration skills in junior high school science learning on temperature, heat, and expansion. The type of research used is Research and Development (R&D). This study use the ADDIE development model consisting of 5 stages, namely analysis, design, development, implementation, and evaluation. The subjects of the trial in this study were 32 students of class VII F MTs Negeri 2 Jember in the 2024/2025 Academic Year in the odd semester. Data collection instruments were carried out using validation sheets, activity implementation sheets, collaboration skills observation sheets, student response questionnaire sheets, interviews, and documentation. Product validation was carried out by 3 validators, product practicality testing was carried out using learning implementation observations, and effectiveness testing was carried out using collaboration skills observation sheets and student response questionnaires. The results of the validation test obtained a score of 87.4% with a very valid category. The results of the practicality test obtained a score of 89.6% with a very practical category. The results of the effectiveness test obtained an N-Gain score of the first collaboration skill of 0.29 with a low category and an N-Gain score of the second collaboration skill of 0.47 with a medium category with an N-Gain difference of 0.18, and an overall student response score of 88.3% with a very effective category.Abstrak: Penelitian ini bertujuan untuk mengetahui kevalidan, kepraktisan, dan keefektifan LKPD berbasis Engineering Design Process (EDP) untuk meningkatkan keterampilan kolaborasi siswa pada pembelajaran IPA SMP materi suhu, kalor, dan pemuaian. Jenis penelitian yang digunakan yaitu Research and Development (R & D). Penelitian ini menggunakan model pengembangan ADDIE yang terdiri dari 5 tahapan yakni analisis, desain, pengembangan, implementasi, dan evaluasi. Subjek pada penelitian ini yakni peserta didik sebanyak 32 siswa kelas VII F MTs Negeri 2 Jember Tahun Ajaran 2024/2025 semester ganjil. Instrument pengumpulan data dilakukan dengan menggunakan lembar validasi, lembar keterlaksanaan kegiatan, lembar observasi keterampilan kolaborasi, lembar angket respon siswa, wawancara, dan dokumentasi. Validasi produk dilakukan oleh 3 validator, uji kepraktisan produk dilakukan menggunakan observasi keterlaksanaan pembelajaran, serta uji keefektifan dilakukan menggunakan lembar observasi keterampilan kolaborasi dan angket respon siswa. Hasil uji validasi mendapatkan skor sebesar 87,4% dengan kategori sangat valid. Hasil uji kepraktisan memperoleh skor sebesar 89,6% dengan kateori sangat praktis. Hasil uji keefektifan memperoleh skor N-Gain keterampilan kolaborasi pertama sebesar 0,29 dengan kategori rendah dan skor N-Gain keterampilan kolaborasi kedua sebesar 0,47 dengan kategori sedang dengan selisih N-Gain sebesar 0,18, serta skor keseluruhan respon siswa sebesar 88,3% dengan kategori sangat efektif.